The Influence of Work Stress and Work-Life Balance on Turnover Intention at PT Gamester Legenda Indonesia - Monia, Angel Serra; Hildayanti, Siti Komariah; Lazuarni, Shafiera (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2025)
The creative industry also has a fast-paced work dynamic and a constant demand for innovation, requiring employees to always be creative and productive, often at the expense of work-life balance, where the boundaries between work time and personal time become blurred. Employees who experience high levels of stress and struggle to maintain work-life balance tend to have a higher turnover intention. This study aims to analyze the effect of job stress and work-life balance on turnover intention among employees of PT Gamester Legenda Indonesia. The research employs a quantitative method and a saturated sample, with a total of 75 respondents consisting of employees of PT Gamester Legenda Indonesia. Data collection was conducted using a questionnaire containing questions related to job stress, work-life balance, and turnover intention. The collected data were analyzed using multiple linear regression, multicollinearity test, t-test, F-test, as well as correlation and determination tests using SPSS Version 26 software. The results indicate that job stress has a significant effect on turnover intention. Meanwhile, work-life balance does not have a significant effect on turnover intention, suggesting that maintaining a balance between work and personal life can reduce employees' desire to change jobs. Overall, both factors have a significant influence on employees' turnover intention at PT Gamester Legenda Indonesia. This study recommends that PT Gamester Legenda Indonesia enhance policies to reduce job stress and pay more attention to employees' work-life balance to lower turnover intention rates. Keywords: Work Stress, Work-Life Balance, Turnover Intention